Comparison of pediatric liver injury unit score and King’s college hospital criteria as a predictor of outcome in children with acute liver failure - Begum, Ferdous Ara; Margana, Iffat; Hassan, M. Nazmul; Siddiqua, Ayesha (International Journal of Contemporary Pediatrics, 2025)
Background: Pediatric acute liver failure (ALF) is a life-threatening condition with high morbidity and mortality, necessitating accurate prognostic tools for early risk stratification. The pediatric liver injury unit (PLIU) Score is a relatively new scoring model developed to improve mortality prediction in pediatric ALF. This study compares PLIU Score and King’s College Hospital Criteria (KCHC) in predicting clinical outcomes in pediatric ALF patients. Methods: This prospective observational study included 28 pediatric ALF patients admitted to a tertiary care hospital in Bangladesh. Clinical and laboratory parameters were assessed at admission, and both KCHC and PLIU Scores were calculated. The primary outcome measure was survival without liver transplantation vs. mortality. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were analyzed for both scoring systems. ROC curve analysis was performed to determine the predictive performance of PLIU Score. Results: Among the 28 patients, 64.29% survived without liver transplantation, while 35.71% succumbed to ALF. Wilson’s disease (50% mortality) and indeterminate ALF (40% mortality) were associated with the highest fatality rates. PLIU Score >233 was significantly correlated with mortality (p=0.04), whereas KCHC showed no significant association with mortality (p=0.09). PLIU Score demonstrated higher sensitivity (80%), specificity (66.7%), PPV (57.1%), and NPV (85.7%) compared to KCHC (40%, 22.2%, 22.2%, and 40%, respectively). ROC curve analysis confirmed the superior predictive ability of PLIU (AUC=0.75) over KCHC. Conclusion: PLIU Score outperforms KCHC in predicting mortality outcomes in pediatric ALF, offering a more reliable prognostic tool for early risk stratification. Its higher sensitivity and predictive accuracy support its potential integration into clinical practice. Future research should focus on validating PLIU Score in larger cohorts and exploring additional biomarkers to enhance its prognostic utility.